(untitled) (E Global Congress, 2023)
Stroke is an extremely common disease throughout the world. Disability from a stroke ranks first among the causes of primary disability, reaching, according to different authors, up to 40%, only 8% of surviving patients are able to return to their previous work after suffering an acute circulatory disorder. To date, the introduction of new methods of treatment contributes to the success of stroke treatment and greater patient survival.